Spatial and Dynamic Evaluation of the Management System of Modern Industrial Enterprises - Prokhorova Viktoriia V.; Koleshchuk Orest Ya. (Problemi Ekonomiki, 2019)
The aim of the article is to develop a framework for spatial and dynamic evaluation of the management system of modern industrial enterprises to affect the level of adaptation to the implementation of innovations. It is determined that the management system of industrial enterprises is complex and has a large number of factors influencing their activities. Spatial and dynamic evaluation of the management system of industrial enterprises makes it possible to identify the problems that confront them and to find a solution to these problems. The paper considers the influence of environmental factors as the basis for spatial and dynamic evaluation of the management system of modern industrial enterprises. The proposed framework for spatial and dynamic evaluation of the management system of modern industrial enterprises is the basis for the formation and adoption of effective management decisions that will allow estimating the quantitative and qualitative changes in space and time; studying the dynamic pattern of the impact of indicators that determine the degree of innovative reflection on activities of industrial enterprises as a framework condition for measuring the level of perception of innovation; determining the level of flexibility, activity and adaptability of industrial enterprises, and their ability to change the external and internal environment.